2021
DOI: 10.3390/biomedicines9101494
|View full text |Cite
|
Sign up to set email alerts
|

Footprints of microRNAs in Cancer Biology

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs involved in post-transcriptional gene regulation. Over the past years, various studies have demonstrated the role of aberrant miRNA expression in the onset of cancer. The mechanisms by which miRNA exerts its cancer-promoting or inhibitory effects are apparent through the various cancer hallmarks, which include selective proliferative advantage, altered stress response, vascularization, invasion and metastasis, metabolic rewiring, the tumor microenvironment and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 254 publications
0
9
0
Order By: Relevance
“…Previously, it was thought that only defects in tumor promoter and tumor suppressive genes play a role in the formation of cancer (Rajasegaran et al 2021). However, with the discovery of miRNA molecules, diagnostic, prognostic, and therapeutic approaches against cancer gained a new dimension (Rajasegaran et al 2021). Accumulating evidence indicates that these small RNA molecules are highly deregulated in human cancers.…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…Previously, it was thought that only defects in tumor promoter and tumor suppressive genes play a role in the formation of cancer (Rajasegaran et al 2021). However, with the discovery of miRNA molecules, diagnostic, prognostic, and therapeutic approaches against cancer gained a new dimension (Rajasegaran et al 2021). Accumulating evidence indicates that these small RNA molecules are highly deregulated in human cancers.…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…Comprehensive understanding of the molecular basis of NPC is necessary to improve treatment and prognosis. Dysregulation of miRNAs signature has been reported in many cancers including NPC, because of the involvement of miRNAs in the regulation of many crucial biological processes 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small and conserved noncoding RNA molecules consisting of 20–22 nucleotides that regulate genes at the level of posttranscription by reducing the targeted mRNAs to induce the partial complementarity of 3′‐untranslated regions. Various pieces of evidence has suggested that miRNAs could function either as onco‐miR or as tumor suppressors‐miR during cancer development 5,7 . miRNAs work in homeostasis under healthy physiological conditions by protecting and regulating biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can modulate the function of various cells and are involved in the pathophysiology of responses to viral infections [ 4 , 5 ] and respiratory diseases [ 6 , 7 ]. In addition, these molecules have been used as biomarkers of diverse diseases [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%